1996
DOI: 10.1007/bf02437842
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of U.S. and Czech/Slovak mental health and health professionals toward five types of sexually explicit materials

Abstract: Mental health and health professionals' attitudes toward sexually explicit materials in the U.S. and Czech/Slovak Republics were investigated. An instrument measuring attitudes toward educational, soft-core, hard-core, violence, and bizarre/paraphiliac sexually explicit materials was administered to sexologists, psychologist/counselors, and medical professionals. These professionals were attending conferences in the U.S. and the Czech/Slovak Republics between November 1992 and September 1993. Mental health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
5
1
Order By: Relevance
“…In sharp contrast to the signi cant differences found between U.S. professionals and Czech and Slovak professionals in their attitudes toward various types of sexually explicit materials (Robinson et al, 1996), U.S. and Czech and Slovak professionals were quite similar in their reports of situations in which sexually explicit materials were useful and not useful. Speci cally, the two groups reported these materials to be most useful in similar settings (i.e., sex education, treating sexual dysfunctions and paraphilias, and sexual permission-giving and shame reduction) and not useful in similar situations (i.e., when the materials cause clients or students to be less accepting of sexuality and when the values of clients or students con ict with the perceived values expressed in the materials).…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…In sharp contrast to the signi cant differences found between U.S. professionals and Czech and Slovak professionals in their attitudes toward various types of sexually explicit materials (Robinson et al, 1996), U.S. and Czech and Slovak professionals were quite similar in their reports of situations in which sexually explicit materials were useful and not useful. Speci cally, the two groups reported these materials to be most useful in similar settings (i.e., sex education, treating sexual dysfunctions and paraphilias, and sexual permission-giving and shame reduction) and not useful in similar situations (i.e., when the materials cause clients or students to be less accepting of sexuality and when the values of clients or students con ict with the perceived values expressed in the materials).…”
Section: Discussioncontrasting
confidence: 64%
“…As we previously reported (Robinson et al, 1996), the best documented nding is that men have more favorable attitudes toward sexually explicit materials than do women (Becker & Byrne, 1985;Cowan & Dunn, 1994;Davis & Bauserman, 1994;Diamond & Dannemiller, 1989;Merritt et al, 1975;Grif tt, 1973;Grif tt & Kaiser, 1978;Hat eld, Sprecher, & Traupmann, 1978;Izard & Caplan, 1974;Kelley, 1985;Leiblum, Rosen, Platt, Cross, & Black, 1993;Mosher, 1973;Schmidt, Sigusch, & Schaefer, 1973;Sigusch, Schmidt, Reinfeld, & Weidemann-Sutor, 1970); some studies, however, have found few or no gender differences (Englar & Walker, 1973;Fisher & Byrne, 1978a, 1978bWinick & Evans, 1994;Robinson et al, 1996). Increased religiosity has been associated with less favorable attitudes toward sexually explicit materials (Athanasiou & Shaver, 1971;Lottes et al, 1993;Robinson et al, 1996;Schmidt et al, 1969;Wallace & Wehmer, 1972), and younger, single, and more educated people have been found to have more favorable attitudes toward sexually explicit materials (Diamond & Dannemiller, 1989;Merritt et al, 1975).…”
supporting
confidence: 54%
See 3 more Smart Citations